2012
DOI: 10.5858/arpa.2011-0321-oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reverse Transcription-Polymerase Chain Reaction, Immunohistochemistry, and Fluorescence In Situ Hybridization Methodologies for Detection of Echinoderm Microtubule-Associated Proteinlike 4–Anaplastic Lymphoma Kinase Fusion–Positive Non–Small Cell Lung Carcinoma: Implications for Optimal Clinical Testing

Abstract: N Context.-Echinoderm microtubule-associated proteinlike 4-anaplastic lymphoma kinase (EML4-ALK) gene fusions are detected in 3% to 13% of non-small cell lung carcinomas. Accurate testing for detection of EML4-ALK fusions is essential for appropriate therapy selection.Objective.-To compare reverse transcription-polymerase chain reaction (RT-PCR), immunohistochemistry (IHC), and fluorescence in situ hybridization (FISH) methodologies for detection of EML4-ALK fusions.Design.-Forty-six pulmonary adenocarcinomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 25 publications
9
104
1
Order By: Relevance
“…The frequency of EML4-ALK translocation variant 1 is approximately 30% [1]. Comparison of FISH, IHC, and RT-PCR methodologies for detecting EML4-ALK translocation variant 1 showed RT-PCR to be the most sensitive [2], as in the current case. The presence of the EML4-ALK fusion gene in lung cancer is mutually exclusive with EGFR and KRAS mutations [1], and patients with EGFR or KRAS gene mutations are unlikely to also harbor the EML4-ALK fusion gene.…”
Section: Discussionmentioning
confidence: 68%
“…The frequency of EML4-ALK translocation variant 1 is approximately 30% [1]. Comparison of FISH, IHC, and RT-PCR methodologies for detecting EML4-ALK translocation variant 1 showed RT-PCR to be the most sensitive [2], as in the current case. The presence of the EML4-ALK fusion gene in lung cancer is mutually exclusive with EGFR and KRAS mutations [1], and patients with EGFR or KRAS gene mutations are unlikely to also harbor the EML4-ALK fusion gene.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, it has been reported that the subtle signal separation because of the chromosomal inversion producing the EML4-ALK translocation variant 1, confirmed by reverse transcription-polymerase chain reaction, is more likely to be missed by FISH. 46 Wallander et al 46 reported that only 1/9 (11%) of variant 1 cases were designated positive by three FISH viewers. Sensitivity and specificity was increased following a combination of scoring FISH break-apart signals that were less than two signal distances apart, and increasing the cutoff to 420% of cells with positive FISH signal patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Its limited use to date is due to the requirement of a quality DNA sample from fresh or frozen tumour tissue. However, new platforms allowing use of routine tissue samples, including paraffin-embedded samples, have been reported [38,39].…”
Section: Methods Of Detectionmentioning
confidence: 99%